If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 = 12s + -5s Combine like terms: 12s + -5s = 7s 35 = 7s Solving 35 = 7s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-7s' to each side of the equation. 35 + -7s = 7s + -7s Combine like terms: 7s + -7s = 0 35 + -7s = 0 Add '-35' to each side of the equation. 35 + -35 + -7s = 0 + -35 Combine like terms: 35 + -35 = 0 0 + -7s = 0 + -35 -7s = 0 + -35 Combine like terms: 0 + -35 = -35 -7s = -35 Divide each side by '-7'. s = 5 Simplifying s = 5
| 0.91=1-9 | | 5y+14=2y-4 | | -12-4k=k+33 | | 3(8-a)-42=27a-6(3+5a) | | 6+2z-1=8z+17-4z | | 3x+(2+x)=66 | | 3(9)-0.5y=5 | | -15m-2=28 | | 118+-5x=-7x+130 | | 7.8y+2=165 | | 13a+-8b=c | | 7x-5x-(8x+6)= | | 8+2y+2x=0 | | 14+m=n | | 6x-(5x+1)= | | 59x-(39x-78)= | | 15x+20y=360 | | 25(2x-3)=125 | | 13x+7=6x+7 | | 2*x-2=22 | | t+.08t=37 | | 6(13+4)= | | 3x+7=-3x+2+2+6x | | 5x^2+4x+1=225 | | 73=2x+7(x-5) | | 6(3.2m-1)=3.6 | | y=-3*1-4 | | (-4x-2)+(13x+1)= | | .111y-4=-9 | | y+8=12(x-6) | | 4*6+x=24 | | 50+75=359 |